Characteristics of head‐up tilt testing with additional adenosine compared with head‐up tilt testing with isoproterenol and isosorbide dinitrate. Issue 6 (22nd March 2014) - Watanabe, Norikazu; Kawasaki, Shirou; Oonishi, Yoshimi; Onuma, Yoshimasa; Munetsugu, Yumi; Itou, Takayuki; Onuki, Tatsuya; Miyoshi, Fumito; Minoura, Yoshino; Adachi, Tarou; Kawamura, Mitsuharu; Asano, Taku; et al.
Abstract: Background: Head‐up tilt (HUT) testing is used to establish the diagnosis of neurally mediated syncope (NMS). Adenosine administration during HUT testing is useful for inducing NMS. However, no comparison between adenosine HUT testing and HUT testing using other drugs has been reported. The purpose of this study was to investigate the clinical usefulness of adenosine compared with isoproterenol (ISP) and isosorbide (ISDN) during HUT testing. Methods: The subjects comprised 103 consecutive patients with unexplained syncope who underwent adenosine and isoproterenol (ISP) HUT tests following a negative response in a drug‐free HUT test. Subjects were first tilted upright at an 80° angle for 30 min and shown to have a negative response in drug‐free HUT test. Subsequently, a continuous bolus of 0.1‐ or 0.2‐mg/kg adenosine was administered while the subjects remained upright and were observed for 5 min (adenosine HUT test). Next, they were tilted upright for 15 min during a continuous infusion of 0.01–0.02 mg/kg min ISP (ISP HUT test). Lastly, they were tilted upright for 15 min after 1.25‐mg ISDN infusion (ISDN HUT test). Results: The diagnostic yield of the adenosine HUT test was 18.1% (18/99) and that of the ISP HUT test was 6.0% (6/99; p =N.S.). Sixty‐one of 99 patients underwent ISDN HUT testing, and 17 patients had a positive response. The diagnostic yield of the adenosine HUT test was 14.7% (9/61) and that of ISDN HUT test was 27.8% ( p <0.05). Five patients had positive responses in both adenosine and ISDN HUT tests. Conversely, 4 patients had a positive response in the adenosine HUT test and a negative response in the ISDN HUT test. Conclusion: The adenosine HUT test was effective in the diagnosis of NMS and is useful as the ISP HUT test for inducing NMS. The diagnostic yield of the adenosine HUT test was not higher than that of the ISDN HUT test. However, the adenosine HUT test took only a few minutes and induced NMS in some of the patients in whom NMS was not induced by the ISDN HUT test. Therefore, performing adenosine HUT testing is worthwhile.